Dealing with next generation infrastructures academic programmes complexity induced resiliency assessment. (14th December 2010) - Calida, Behnido Y.; Gheorghe, Adrian V.; Unal, Resit; Vamanu, Dan
Academic departments in the field of critical societal infrastructures need to assess and upgrade their existing programmes and course offerings for several important reasons such as: 1) to regularly assess a curricula's structure; 2) to maintain competitiveness; 3) to assess the resiliency of a given academic programme; 4) to ensure its relevance to the fast changing environment and context among others. This paper aims to demonstrate the complexity-derived concept of 'resiliency' and how decision making applies to difficult decision making situations, with respect to the need of continuous improvement of graduate academic programmes. We use a graph theory-based complexity perspective as a tool to supplement decision making in assessing a department's course offering. Specifically, we can regard a graduate programme offering as a multi-component (many body) system consisting of its internal connectivity (i.e., combination of course offering as member interactions) defining structural complexity and as a source of vulnerability, hence resiliency. We explore an alternate methodology which combines the state-of-the-art in clustering text analysis as well as complexity-induced vulnerability quantitative methodologies recently used in performance quantification of complex systems.